TMEM126A, Encoding a Mitochondrial Protein, Is Mutated in Autosomal-Recessive Nonsyndromic Optic Atrophy - Hanein, Sylvain (Elsevier, 2009)
Nonsyndromic autosomal-recessive optic neuropathies are rare conditions of unknown genetic and molecular origin. Using an approach of whole-genome homozygosity mapping and positional cloning, we have identified the first gene, to our knowledge, responsible for this condition, TMEM126A, in a large multiplex inbred Algerian family and subsequently in three other families originating from the Maghreb. TMEM126A is conserved in higher eukaryotes and encodes a transmembrane mitochondrial protein of unknown function, supporting the view that mitochondrial dysfunction may be a hallmark of inherited optic neuropathies including isolated autosomal-recessive forms.